2014
DOI: 10.1002/jbm.b.33247
|View full text |Cite
|
Sign up to set email alerts
|

Comparing PMMA and calcium sulfate as carriers for the local delivery of antibiotics to infected surgical sites

Abstract: Antibiotic-loaded bone cement is a primary option for treatment of orthopedic infections. Poly(methyl methacrylate) (PMMA) is a widely used cement that, when loaded with antibiotics in spacer or bead form, has been shown to reduce infection rates. However, PMMA is not resorbable and requires a second surgery for removal, while also acting as a potential foreign body for bacterial colonization. Alternatively, resorbable bone cements, such as calcium sulfate, have been proposed and present the advantage of being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 22 publications
5
98
0
1
Order By: Relevance
“…In an in vitro study, McConoughey et al (13) found that calcium sulfate beads achieved similar or a more improved efficacy compared to the PMMA beads in inhibiting bacterial growth. Grimsrud et al (23) reported similar characteristics of in vitro elution between voriconazole-loaded PMMA bone cement and calcium sulfate bone substitute.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In an in vitro study, McConoughey et al (13) found that calcium sulfate beads achieved similar or a more improved efficacy compared to the PMMA beads in inhibiting bacterial growth. Grimsrud et al (23) reported similar characteristics of in vitro elution between voriconazole-loaded PMMA bone cement and calcium sulfate bone substitute.…”
Section: Discussionmentioning
confidence: 99%
“…iii) With regards to the definitive outcomes of the combination of calcium sulfate with additives in reconstruction of bone defects, Howlin et al (18) identified that calcium sulfate with antibiotics may have a potential ability to reduce or eliminate biofilm formation on adjacent periprosthetic tissue and prosthesis material, thus reducing the rates of periprosthetic infection. Following the comparison of PMMA with calcium sulfate as antibiotic carriers at the infected sites, McConoughey et al (13) indicated that calcium sulfate led to similar or improved outcomes compared to PMMA in the inhibition of bacterial growth. In a pilot study regarding the assessment of clinical outcomes of grafted sockets using either calcium sulfate-PRP or calcium sulfate alone in the socket preservation procedure, Cheah et al (19) reported that calcium sulfate-PRP-grafted sites had a higher mineralized bone content compared to the calcium sulfate-grafted sites.…”
Section: Calcium Sulfate Can Induce the Formation Of Membranementioning
confidence: 99%
See 2 more Smart Citations
“…Antiinfective biomaterials are increasingly used as an adjunctive strategy to prevent implanted biomaterial infections and to inhibit biofilm-forming microorganisms [13,27,44,49,55,63,64]. Commonly used local antibiotic delivery systems range from antibiotic-loaded bone cement to calcium-based drug delivery systems to sprinkling antibiotics within the wound site [8,24,40,42]. Recent developments have been focused on degradable and customizable local delivery strategies to ensure coverage of the wound, effective antibiotic elution, and minimization of secondary procedures [15,30,60].…”
Section: Introductionmentioning
confidence: 99%